Incorporating Patient Preferences into Medical Device Benefit-Risk Assessments. (2nd July 2016) - Irony, Telba; Ho, Martin; Christopher, Stephanie; Levitan, Bennett
Abstract: Patients play a unique role in medical device evaluation because they live with their conditions and consequences of the treatments they choose. They may weigh the benefits, risks, and other attributes of treatments differently than physicians and regulators. They may even be heterogenous among themselves when trading-off benefits and risks. Therefore, industry, regulators, and patient groups have a growing interest in exploring how to assess and incorporate patient preferences when conducting benefit-risk assessments of medical devices. This article discusses remarkable developments in this area: a proof-of-concept study on preferences of obese patients conducted by the Center for Devices and Radiological Health at the FDA (CDRH), the guidance documents on factors for benefit-risk determinations and on patient preference information issued recently by CDRH, and the Patient-Centered Benefit-Risk project developed by the Medical Device Innovation Consortium. We will also discuss important concepts related to patient preferences and use the CDRH study results to illustrate them.